Analisis Pola Aliran dan Muka Air Tanah di Irigasi Bili-Bili Menggunakan Surfer 25 - Nurnawaty; Nur Isra; Amrullah Mansida (Jurnal Karajata Engineering, 2026)
Groundwater is essential for supporting irrigation activities and agricultural sustainability. The presence of secondary irrigation canals can influence groundwater flow patterns and groundwater level conditions in the surrounding areas. This study aims to analyze the groundwater flow pattern and changes in groundwater table elevation around the secondary canal in the Bili-Bili Irrigation Area, Gowa Regency, South Sulawesi. The research used a quantitative descriptive method through field observations and groundwater measurements at several observation points. The collected data included coordinates, land elevation, and groundwater depth, which were analyzed using Surfer 25 software to generate contour maps and determine groundwater flow directions. The results showed that groundwater flow patterns initially spread irregularly, but later became more directed toward the secondary canal, indicating that the canal functions as a groundwater discharge zone. Groundwater table elevation changes ranged from 34 cm to 44.9 cm between upstream and downstream areas. These findings indicate that hydraulic gradients and topographic conditions affect groundwater movement around irrigation channels.